2023
DOI: 10.1667/rade-22-00149.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Raman Spectroscopy and Covariate-Adjusted Multivariate Analysis for the Detection of Irradiated Blood

Abstract: Biological dosimetry is a key technique for retrospective radiation dosimetry that provides individual estimates of absorbed dose of ionizing radiation, applicable for use in a large scale radiological/nuclear event. Current techniques for biodosimetry are labor intensive and time consuming and not high through-put. In this proof-of-concept study, we developed a new approach for detecting irradiated blood based on Raman spectroscopy of blood combined with multivariate analysis. Peripheral blood samples from 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Raman spectroscopy has shown promising potential to identify the effects of ionizing radiation in blood and blood components 6,7 . In a recent pilot study involving blood from 8 healthy donors, our work demonstrated the application of RS and multivariate analysis for the separation between 0 and 5 Gy irradiated whole blood 5 . The effects of ionizing radiation were shown to correspond to changes in the Raman intensity contributions from hemoglobin, proteins, and lipids, with the hemoglobin signal dominating the Raman spectrum.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Raman spectroscopy has shown promising potential to identify the effects of ionizing radiation in blood and blood components 6,7 . In a recent pilot study involving blood from 8 healthy donors, our work demonstrated the application of RS and multivariate analysis for the separation between 0 and 5 Gy irradiated whole blood 5 . The effects of ionizing radiation were shown to correspond to changes in the Raman intensity contributions from hemoglobin, proteins, and lipids, with the hemoglobin signal dominating the Raman spectrum.…”
Section: Introductionmentioning
confidence: 92%
“…However, it is technically challenging, labour-intensive, and time-consuming 2 . To address these limitations, many other techniques for determining absorbed radiation dose are currently being explored such as genomic 2,3 and automated cytogenic 4 techniques, as well as Raman spectroscopy 5,6 .…”
Section: Introductionmentioning
confidence: 99%